2003
DOI: 10.1074/jbc.m303064200
|View full text |Cite
|
Sign up to set email alerts
|

DC3, the Smallest Subunit of the Chlamydomonas Flagellar Outer Dynein Arm-docking Complex, Is a Redox-sensitive Calcium-binding Protein

Abstract: The outer dynein arm-docking complex (ODA-DC) targets the outer dynein arm to its correct binding site on the flagellar axoneme. The Chlamydomonas ODA-DC contains three proteins; loss of any one prevents normal assembly of the outer arm, leading to a slow, jerky swimming phenotype. We showed previously that the small-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Their flagella lack the outer dynein arms and beat with roughly one-half wild-type frequency. However, oda1 also lacks the outer dynein arm docking complex proteins, which include a potential Ca 2+ sensor (Casey et al, 2003a;Casey et al, 2003b). The results of all analyses for all strains and conditions tested are presented in tabular form in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their flagella lack the outer dynein arms and beat with roughly one-half wild-type frequency. However, oda1 also lacks the outer dynein arm docking complex proteins, which include a potential Ca 2+ sensor (Casey et al, 2003a;Casey et al, 2003b). The results of all analyses for all strains and conditions tested are presented in tabular form in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we have previously shown that the C1 microtubule of the central apparatus is not oriented towards the region of active sliding in either pf28 or oda1 axonemes, indicating that in the absence of the outer dynein arms, regulatory cues produced by the central apparatus are uncoupled from microtubule sliding under high Ca 2+ conditions (Wargo and Smith, 2003). While pf28 axonemes lack the outer dynein arms, which is the same defect as in oda1, oda1 axonemes additionally lack the outer dynein arm docking complex, which includes DC3, a Ca 2+ sensitive binding protein (Casey et al, 2003a;Casey et al, 2003b). These results suggest a possible role for DC3 in modulating dynein-driven microtubule sliding in response to increases in Ca 2+ .…”
Section: Sliding Pattern Correlates With Waveformmentioning
confidence: 93%
See 1 more Smart Citation
“…It is possible that some second messengers affect motility by additional mechanisms that are independent of phosphorylation. For example, several subunits of dynein motors are EF-hand proteins that may bind calcium directly, altering dynein activity [Piperno et al, 1992;King and Patel-King, 1995;Yanagisawa and Kamiya, 2001;Casey et al, 2003;Guerra et al, 2003]. Chemical signaling also includes axonemal enzymes that are not directly sensitive to second messengers including casein kinase 1 (CK1), PP1, and PP2A, all of which appear to be involved in the control of dynein-driven motility [Walczak and Nelson, 1993; Central apparatus-associated polypeptides PF6 238-kDa alanine/proline rich protein; pf6 flagella lack the 1a projection on the C1 microtubule and display only twitching motion [Dutcher et al, 1984;Rupp et al, 2001] PF16 57-kDa armadillo repeat containing protein that localizes to the c1 microtubule; pf16 flagella lack the C1 microtubule and are paralyzed.…”
Section: Conserved Signaling Proteins Located In the Central Pair Andmentioning
confidence: 99%
“…DC1 and DC2 are coiled-coil proteins; they are essential for the OAD docking activity because mutants (oda1, oda3) lacking these proteins entirely lack OAD. In contrast, DC3 is a redox-sensitive Ca 2+ -binding protein and apparently is nonessential for OAD binding because a mutant (oda14) lacking it retains ∼40% of OADs (20,21). Presumably, DC3 has an as yet unidentified regulatory function.…”
mentioning
confidence: 99%